2013
DOI: 10.2174/1874192401307010076
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Stenosis Associated with Increased Mortality in Patients who Underwent Coronary Artery Bypass Grafting: A Single Center Experience

Abstract: Background: Vascular disease resulting from arteriosclerosis is a severe worldwide health risk. Early diagnosis and intervention is important to control adverse cerebral and cardiovascular events. The aim of this study was to assess the potential predictors of mortality in patients submitted to coronary bypass surgery.Methods: Cohort study included asymptomatic cerebrovascular disease patients scheduled for coronary artery bypass grafting admitted to the cardiology reference center. All patients were submitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…15 The 2011 European peripheral artery disease (PAD) strategies extended their recommendation for preoperative duplex scan for CAS in CABG patients to include patients more than 70 years of age or those with evidence of carotid bruit, multi-vessel CAD, cerebrovascular disease, or PAD class I evidence. 16 DaRosa et al 17 noted that the perioperative risk of stroke after cardiac surgery was 3.8%–7.4% among the patients with more than 50% CAS; moreover, they reported increasing prevalence with more than 70% carotid lesion, which is similar to our study results. In a retrospective cohort of 1558 Chinese patients who underwent CABG, the prevalence of CAS with ⩾50% and ⩾70% stenosis were 21.2% and 6.7%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…15 The 2011 European peripheral artery disease (PAD) strategies extended their recommendation for preoperative duplex scan for CAS in CABG patients to include patients more than 70 years of age or those with evidence of carotid bruit, multi-vessel CAD, cerebrovascular disease, or PAD class I evidence. 16 DaRosa et al 17 noted that the perioperative risk of stroke after cardiac surgery was 3.8%–7.4% among the patients with more than 50% CAS; moreover, they reported increasing prevalence with more than 70% carotid lesion, which is similar to our study results. In a retrospective cohort of 1558 Chinese patients who underwent CABG, the prevalence of CAS with ⩾50% and ⩾70% stenosis were 21.2% and 6.7%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Extracranial carotid artery stenosis (CAS) is a risk factor for perioperative stroke in patients undergoing CABG surgery [34]. In patients with 50% to 80% stenosis of the carotid arteries, the incidence of stroke after CABG ranged from 3% to 10%, and approached 22% in patients with >80% stenosis [35].…”
Section: Extra-cardiac Arteriopathymentioning
confidence: 99%
“… 4 In previous studies of CABG patients with 50% to 80% stenosis of the carotid arteries, the incidence of stroke ranged from 3% to 10%, and approached 22% in patients with >80% stenosis. 5 , 6 A recent meta-analysis of American and European studies of CAS found that the risk of perioperative stroke following cardiac surgery ranged from 3.8% to 7.4% in patients with ≥50% stenosis, increasing to 2% to 9.1% in those with ≥70% stenosis. 7 Mortality rates of 3.6% to 15.8% have also been reported in CABG patients with CAS.…”
Section: Introductionmentioning
confidence: 99%